Thermoelectric Performance: Enhancement of Thermoelectric Performance in CuSbSe2 Nanoplate‐Based Pellets by Texture Engineering and Carrier Concentration Optimization (Small 50/2018). Issue 50 (13th December 2018) - Luo, Yubo; Du, Chengfeng; Liang, Qinghua; Zheng, Yun; Zhu, Beibei; Hu, Huanlong; Khor, Khiam Aik; Xu, Jianwei; Yan, Qingyu; Kanatzidis, Mercouri G.
Abstract : In article number1803092, Qingyu Yan, Mercouri G. Kanatzidis, and co‐workers develop a bottom‐up self‐assembly process to prepare CuSbSe2 ‐PtTe2 based pellets with highly oriented single‐crystalline nanoplates, which results in an orientation factor of ≈0.8 for (00l) facets. The texture engineering and carrier concentration optimization enable an ≈500% enhanced ZT value (0.50 at 673 K) for CuSbSe2 ‐2.0 mol% PtTe2 compared to pure CuSbSe2 .